The Antecedents and Consequences of Online Impulse Buying during Pandemic COVID-19 Do consumers regret after doing online impulse buying - Hevitara Wulandari; Renny Risqiani (Universitas Trisakti, 2021)
Online shopping became a consumer choice during the covid 19 pandemic, this study aims to analyze the antecedents and consequences of impulsive purchases at online stores during the covid 19 pandemic. Data were collected online from 202 respondents who had made purchases at e-stores in Jakarta and surrounding areas. The data were analyzed using structural equation modeling. The results showed that flow state had a positive and significant effect on online impulse buying, while risk perception and customer satisfaction had no significant effect. However, customer satisfaction is influenced by perceived usefulness and E-store performance confirmation, while flow state is influenced by task skills and task challenges. The results of the last hypothesis in this study, found a positive effect of online impulse buying on post-purchase regret.